Hukum Islam di Indonesia, mungkinkah ? - Marluwi Marluwi (Justicia Islamica, 2006)
This study aims to analyze the possibility of applying Islamic law in Indonesia in the context of a pluralistic national legal system. As a Muslim-majority country, the application of Islamic law is an evolving discourse, especially in the aspects of family, economic, and criminal law. This study uses a qualitative method with a literature study approach, examining the constitution, laws and regulations, as well as the thoughts of scholars and academics. The results of the study show that Islamic law has been accommodated in several regulations, such as the Islamic Law Compilation (KHI) and Islamic banking. However, the comprehensive application of Islamic law faces challenges from political and social aspects, and the principle of diversity. This study emphasizes that although Islamic law has the opportunity to be applied, a contextual and inclusive approach is needed to remain in harmony with the values of justice and Indonesian nationality.